Transformation by the mark - Lenaway, Scott R., author; Dormer, James, advisor; Simons, Stephen, advisor; Emami, Sanam, committee member; Moseman, Eleanor, committee member; Ore, Janet, committee member (Colorado State University. Libraries, 2013)
The earliest elements of art have been the mark making found in painting and drawing. From the cave paintings created in France 40,000 years ago to the modern day, the use of line and mark making in the rendering of an object is still of importance. Technology will always play a role in society, which in turn carries over into it's art. Modern artists have found methods to incorporate technology influence in their work and process. Artists must not forget the importance of line. In my thesis work the importance of line and mark making is a key element in my work. Using industrial made objects and environments, I explored the relationship between the handmade marks of an artist and industrially created objects. As modern technology has had a great effect upon the production of industrial objects, it has dehumanized the worker. In contrast, the lines and marks that an artist creates reflect the human aspect of art and life.